PENGARUH FAKTOR KONSEP KENDIRI, KESEDARAN KOMUNITI DAN SOKONGAN SOSIAL TERHADAP PENGINTEGRASIAN SOSIAL BAGI PESALAH MUDA DI MALAYSIA - Tharshini, N. K.; Fauziah, Ibrahim; Mohd Suhaimi, Mohamad; Ezarina, Zakaria (Penerbit Universiti Sains Malaysia, 2021)
Social integration is an important aspect to prevent young offenders from being involved in criminal activities and motivates them to lead a positive lifestyle. Therefore, this article discusses the influence of self-concept, sense of community and social support towards social integration among young offenders in Malaysia. Data were collected using a quantitative approach based on cross-sectional survey design among 306 young offenders undergoing Community Service Order initiated by the Department of Social Welfare. The resultant data were analysed using IBM for SPSS version 23.0. A majority of respondents who took part in this study consisted of male young offenders aged 20 years old, single in marital status, completed educational level up to Sijil Pelajaran Malaysia (SPM), were unemployed and were involved in theft. The findings via multiple regression analysis indicate that social support (β = 0.440, p < 0.01) is the main factor that contributes to social integration among young offenders. As an overall impact, the study’s implications to concerned parties include calls to improve the existing module and rehabilitation programme in order to help young offenders succeed in the process of social integration.